The Effect of Integrated Nutrition Services on the Bodyweight of Underweight Children in Tanah Garam Health Center Coverage Area, Solok City, West Sumatera - Umar, Hermita Bus; Dianti, Nova; John Amos; Gusnedi; Zulferi (proceedinginternational, 2023)
Being underweight in children under five in Indonesia is still high. Integrated nutrition service is one of the innovative programs to overcome the underweight problem among under-five children. This study aims to determine the effect of integrated nutrition services on the bodyweight of underweight under-five children in Tanah Garam Health Center, Solok City. The study used a pre-experimental one-group pretest-posttest design. As the study subject, we recruited 30 healthy underweight children (WAZ -2<x<-3SD). Data collection includes body weight before and after the 10-days intervention. The body weight difference was analyzed using the dependent t-test. There was a significant change in children's weight as seen from the increase in the weight for age Z score (WAZ) after the provision of integrated nutrition service (P<0.05). About 76% of the subjects had bodyweight improvement. The mean body weight increase from baseline to end line was 0,25±1,17 kg, while the WAZ increased from -2.32 to -2.12 The implementation of integrated nutrition service could potentially improve the bodyweight of underweight children. It is recommended that all healthy underweight children participate in implementing the program.